2022
DOI: 10.1186/s12872-022-02787-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of patients with septic shock-triggered Takotsubo syndrome: a single-center 7 case series

Abstract: Background Myocardial dysfunction is common in septic shock and has long been recognized. Takotsubo syndrome is an acute and usually reversible myocardial injury without evidence of an obstructive coronary artery disease, yet little is known about this syndrome in septic shock patients. Case presentation Among 84 septic shock patients admitted to the ICU over a period of 8 months, 7 patients (8.3%) were diagnosed with Takotsubo syndrome. The percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…One study did identify sepsis secondary to TTS, but no study to date has identified if the preceding combination of sepsis with its noradrenaline treatment can trigger TTS. 30 Coronavirus disease 2019 and precipitating factors of takotsubo syndrome Given the current climate, it is worthwhile to investigate a link, or lack thereof, between COVID-19 and TTS. As such, literature in the field has pursued this idea.…”
Section: Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…One study did identify sepsis secondary to TTS, but no study to date has identified if the preceding combination of sepsis with its noradrenaline treatment can trigger TTS. 30 Coronavirus disease 2019 and precipitating factors of takotsubo syndrome Given the current climate, it is worthwhile to investigate a link, or lack thereof, between COVID-19 and TTS. As such, literature in the field has pursued this idea.…”
Section: Stressmentioning
confidence: 99%
“…It would be interesting to see hyperinflammatory states, like sepsis, interacting with catecholamines, where its administration here is common. One study did identify sepsis secondary to TTS, but no study to date has identified if the preceding combination of sepsis with its noradrenaline treatment can trigger TTS 30 …”
Section: Risk Factorsmentioning
confidence: 99%
“…5 More recently, observational studies have suggested that, in many cases, myocardial dysfunction in sepsis might be a stress-induced cardiomyopathy. 6, 7 Sepsis can also result in a high catecholaminergic state in animal models due to intrinsic catecholamine release and extrinsic administration. In an awake murine cecal ligation model of sepsis where no exogenous catecholamines were administered, high levels of catecholamines were still detected due to endogenous release.…”
Section: Introductionmentioning
confidence: 99%
“…Given the large body of supportive preclinical and clinical evidence suggesting that the myocardial depression of sepsis is a form of stress-induced cardiomyopathy, we decided to investigate this hypothesis. 5, 6 Since, in patients with septic shock exhibiting life-threatening hypotension, it is neither possible nor ethical to withhold exogenous catecholamines or use sedatives and narcotics to suppress any stress-induced catecholamine response, we therefore utilized a canine model of sepsis which simulates the cardiovascular changes of human septic shock 5, 6 to examine the impact of altering levels of catecholamines. In the published literature, epinephrine and isoproterenol have most commonly been used to create stress-induced cardiomyopathies in animal models, we chose epinephrine because it is also used clinically to treat septic shock.…”
Section: Introductionmentioning
confidence: 99%